PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN MARINA HAND AND BODY LOTION DI SEMARANG - Tri Novi Yani; Imam Nuryanto (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2021)
There are several factors that influence purchasing decisions, namely brand equity and consist of brand awareness, brand association, perceived quality and brand loyalty. The object of this research is Marina hand and body lotion based on the Top brand index in 2014-2018, Marina hand and body lotion are the only hand and body brands that are always increasing. The purpose of this research was to analyze the influence of brand awareness, brand association, perceived quality and brand loyalty on purchasing decisions. The population in this research were consumers who had bought and used Marina hand and body lotion which was domiciled in Semarang and 17 years old. The sample used was 104 respondents. sampling technique by purposive sampling. The type of data used is primary data, the data collection method used a questionnaire and the analysis technique used is multiple linear regression. The results of the analysis show that brand equity: brand awareness, brand association, perceived quality and brand loyalty have a positive and significant influence on purchasing decisions.